Is it always necessary to perform an axillary lymph node dissection after neoadjuvant chemotherapy for breast cancer? - Osorio-Silla, I (Ann R Coll Surg Engl, 2019)
INTRODUCTION: Recent prospective studies support the feasibility of performing sentinel lymph node biopsy following neoadjuvant chemotherapy in initially fine-needle aspiration cytology or ultrasound-guided biopsy-proven node-positive breast cancer. The main aid is to identify preoperative features that help us predict a complete axillary response to neoadjuvant chemotherapy in these patients and thus select the candidates for sentinel lymph node biopsy post-neoadjuvant chemotherapy to avoid unnecessary axillary lymphadenectomy. MATERIALS AND METHODS: A retrospective observational study with a total of 150 patients, biopsy-proven node-positive breast cancer who underwent neoadjuvant chemotherapy followed by breast surgery and axillary lymphadenectomy were included and retrospectively analysed. A predictive model was generated by a multivariate logistic regression analysis for pathological complete response-dependent variable. RESULTS: The response of the primary lesion to neoadjuvant chemotherapy according to post-treatment magnetic resonance imaging, Her2/neu overexpression and a low estrogen receptor expression are associated with a higher rate of nodal pathologically complete response. The multivariant model generated a receiver operating characteristic curve with an area under the curve of 0.79 and a confidence interval of 0.72–0.87 at a 95% level of significance. CONCLUSIONS: This model could be a helpful tool for the surgeon to help in predicting which cases have a higher likelihood of achieving a pathologically complete response and therefore selecting those who may benefit from a post-neoadjuvant chemotherapy sentinel lymph node biopsy and avoid unnecessary axillary lymphadenectomy.